Green synthesized gold nanoparticles from Pseudobulbus Cremastrae seu Pleiones show efficacy against hepatic carcinoma potentially through immunoregulation - Junmo Zhu; Zijing Liu; Youwei Pu; Jie Xu; Sitong Zhang; Yixi Bao (Taylor & Francis Group, 2022)
Nanobiotechnology, the interface between biology and nanotechnology, has recently emerged in full bloom in the medical field due to its minimal side-effects and high efficiency. To broaden the application of nanobiotechnology, we composed gold nanoparticles from the extract of Pseudobulbus Cremastrae seu Pleiones (PCSP) using an efficient and green procedure. The biosynthesized Au nanoparticles containing PCSP (PCSP-AuNPs) were characterized by UV-vis spectroscopic, transmission electron microscopy (TEM), atomic force microscopy (AFM), dynamic light scattering (DLS), Fourier transform infrared spectroscopy (FT-IR), and Energy Dispersive X-ray (EDAX). After verifying the stability of PCSP-AuNPs, we detected its biosafety and immune-modulatory effects on RAW264.7 in vitro using NO assay, ELISA (TNF-α, IL-12p70, and IL-1β), and CCK-8 test. Furthermore, we examined the direct in vitro effects of PCSP-AuNPs on hepatocellular carcinomas (HCCs). Finally, we evaluated the immune regulation of PCSP-AuNPs using a mouse model with H22-tumor by testing the index of immune organs, splenic lymphocyte proliferation, cytokines levels (TNF-α and IL-10), and the CD4+/CD8+ cell ratio in the peripheral blood. Immunohistochemical analyses including H&E and PCNA staining were performed to investigate the anti-cancer efficacy and biocompatibility of PCSP-AuNPs. We found that PCSP-AuNPs not just possessed low toxicity, but also improved the immune-mediated antitumor response as compared to PCSP alone, suggesting its potential as a novel and efficient drug for liver cancer therapy.